Study of Interstitial Lung Disease With Reference to Radiological Profile - Annapurna, S.; Badarke, Pankaj; Chandra, Eshwar (Asian Journal of Medical Radiological Research, 2018)
Background: Interstitial lung disease Diagnosis requires extensive investigation into the patient’s symptoms, life style, work history, exposures, and medications forming the clinical context. Subjects and Methods: The cross sectional perspective and high spatial resolution makes HRCT superior to other imaging modalities like chest X-Ray, lung tomography and conventional CT Scanning multiplanar imaging with aim to determine the radiological profile in a clinically suspected cases of Interstitial Lung Disease the present study conducted over 50 patients during the period of 12 months from October 2012 to October 2013 in kamineni hospital, Hyderabad. Results: Out of 50 clinically suspected patients of interstitial lung disease, a specific pattern was observed in 44patients on HRCT and 33 patients on chest radiograph. Patterns found on chest radiograph were correlated with patterns found on HRCT. Out of 44 interstitial lung diseases on HRCT, 28 patients revealed correlation between chest radiograph and HRCT pattern. Out of 50, thirty one patients had correlation between Chest radiograph and HRCT findings. Conclusion: HRCT is superior to chest radiograph in detection of all basic patterns associated with ILD and scores more in their distribution and lung parenchymal involvement.